Characterizing polar mobilities to understand the role of weather, water, ice and climate (WWIC) information - Stewart, Emma J.; Liggett, Daniela; Lamers, Machiel; Ljubicic, Gita; Dawson, Jackie; Thoman, Rick; Haavisto, Riina; Carrasco Cerda, Jorge Fernando (My University, 2020)
The Polar Regions are undergoing rapid environmental change while simultaneously witnessing growth and diversification of human activity. These changes call for more responsive, detailed and specialized weather, water, ice and climate (WWIC) information services so that the risks related to human activities can be minimized. Drawn from an extensive literature review this article provides an examination of selected sectors and their uses of WWIC information services in order to offer an initial understanding of diverse environmental forecasting needs. Utilizing a mobilities perspective we provide a characterization of mobility in the Polar Regions to help contextualize current WWIC uses and needs. Using four illustrative case studies of polar mobilities (community activities; cruise tourism; shipping; and government and research operations) the article explores two broad questions: (1) How are mobilities characterized in the Polar Regions? (2) What is known about the role of WWIC information in Polar mobilities? The findings suggest an incongruence between the information provided and the ways in which WWIC information is both used and needed by various sectors. Knowledge gaps are outlined that suggest more efforts are needed to understand the highly complex set of interconnections between WWIC users, providers, mobilities and decision-making across the Polar Regions.
Keywords: weather; water; ice and climate (wwic) information; polar regions; mobilities; mobile sectors; information needs; climate services